Isolated hepatic tuberculosis: A rare cause of hepatic mass lesions - Nurten Türkel Küçükmetin; Ümit İnce; Bahattin Çiçek; Haluk Akman; Güngör Boztaş; Nurdan Tözün (Turkish Journal of Gastroenterology, 2019)
Hepatic tuberculosis usually accompanies pulmonary and extrapulmonary tuberculosis. Although isolated hepatic tuberculosis is a very rare condition, it should be considered in the differential diagnosis of a hepatic mass. Here, we report a 42-year-old woman presenting with weight loss, fever, night sweats, and a hepatic mass on the abdominal ultrasonography and magnetic resonance imaging (MRI). Ultrasonography-guided percutaneous needle biopsy demonstrated a caseating granuloma with epithelioid histiocytes and giant cells compatible with the diagnosis of tuberculosis. The patient was treated with four anti-tuberculous drugs for 1 year. She recovered clinically, and her post-treatment abdominal MRI was normal. Turkish Başlık: İzole Hepatik Tüberküloz: Hepatik kitle lezyonlarının nadir görülen bir sebebi Anahtar kelimeler: İzole hepatic tüberküloz, karaciğer kitlesi, ayırıcı tanı Hepatik tüberküloz pulmoner ya da ekstrapulmoner tuberküloza eşlik eder. İzole hepatik tüberküloz oldukça nadir olmakla birlikte, karaciğer kitlelerinin ayırıcı tanısında akılda tutulmalıdır. Biz burada kilo kaybı, ateş, gece terlemesi ile başvuran, batın ultrasonografisi ve magnetik rezonans (MR) görüntüleme incelemesinde hepatik kitle görülen hastamızı sunduk. Hastada ultrasonografi eşliğinde alınan karaciğer biyopsi örneğinde, kazeifikasyon nekrozu ile uyumlu nekroz, mononükleear iltihabi hücreler ve çevrede dev hücreler görüldü ve bir yıl süre ile dörtlü antitüberküloz tedavi uygulandı. Tedavi sonrasında hem klinik hem de karaciğer MR görüntülerinde iyileşme saptandı.